MEDICINAL ORCHIDS AND THEIR SIGNIFICANCE IN IMMUNITY DEVELOPMENT - Wang, Y (International Journal of Allied Sciences (IJAS), 2023)
Orchids, one of the largest families of flowering plants, have been long used in traditional medicine systems such as Ayurveda and traditional Chinese medicine. Recent studies have identified them as a rich source of chemical constituents with promising anti-inflammatory, antidiabetic, antiviral, and anticancer properties. Medicinal orchids belong mainly to the genera Calanthe, Coelogyne, Cymbidium, Cypipedium, Dendrobium, Ephemerantha, Eria, Galeola, Gastrodia, Gymnadenia, Habenaria, Ludisia, Luisia, Nevilia, and Thunia. Orchid phytochemicals include stilbenoids, anthraquinones, pyrenes, coumarins, and flavonoids, which play vital roles in immunity development and curing critical ailments. Several orchid species have been used for their immunomodulatory properties in traditional medicine, including Bletilla striata, Corallorhiza maculata, Corymborchis longiflora, Dactylorhiza hatagirea, and Malaxis muscifera. The authors suggest that further studies can identify new biomolecules for developing new therapeutics and expanding the use of traditional remedies to modern medical practices. Orchid’s species contain a large number of bioactive phytochemicals that can be used as a promising source of medicine. Orchids can be used in treatment of conditions such as neurodegenerative disorders, anticonvulsive, anticancer, antidiabetic, viral diseases, etc. Orchids have recently been proved to be a rich storehouse of chemical constituents with promising anti-tumor, anti-cancer, and anti-inflammatory activities as revealed in modern biology based studies